FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN TIMELINESS ATAS PENYAMPAIAN LAPORAN KEUANGAN - Panjaitan, Zooana Farida; Wahidahwati, Wahidahwati; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This study aimed to test, analyze, and obtain empirical evidence of the level of profitability, total assets turnover ratio, leverage, firm size, the firm size, liquidity, opinion type, the length of a client company KAP, the company has subsidiaries and contingent effect on audit delay and timeliness.Based on the analysis that the liquidity effect on audit delay, but does not affect the timeliness. Firm size, the type of opinion, and contingencies no effect on audit delay but bepengaruh to timeliness. Level of profitability, asset turnover, size of company, effect on audit delay and timeliness. Leverage, Being Old Firm Client, The Company Has Subsidiaries, has no effect on audit delay and timeliness.Keywords : Audit delay, Timeliness